Prison and the brain: Neuropsychological research in the light of the European Convention on Human Rights. Issue 3 (September 2019) - Ligthart, Sjors; van Oploo, Laura; Meijers, Jesse; Meynen, Gerben; Kooijmans, Tijs
Prison is by its nature a deliberately impoverished environment, with few physical, mental and social activities. Various studies have shown negative effects of an impoverished environment on animal as well as human brain functions. A recent study in a Dutch remand prison showed that brain functions connected with self-regulation decline after 3 months of imprisonment. Reduced self-regulation appears to be a risk factor for recidivism. In this article, we examine the legal implications of these neuropsychological findings in a European context. Firstly, we analyse these results in the light of the principle of rehabilitation as interpreted in case law of the European Court of Human Rights. Secondly, we explore how the neuropsychological insights could be relevant in the context of the prohibition of torture, inhuman and degrading treatment (Article 3 of the European Convention on Human Rights (ECHR)). We argue that if the impoverished prison environment hampers rehabilitation, states are positively obliged to take appropriate measures to counter these effects. Ultimately, negative effects on brain functioning by impoverished prison environments could even raise an issue under Article 3 ECHR. Furthermore, we argue that neuropsychological insights have to be taken into account when establishing the threshold according to which the European Court on Human Rights judges prison conditions. We conclude that in the light of these considerations further research on the neuropsychological effects of the prison environment is required.